Enhanced electrochemical performance of sodium cathode materials with partial substitution of Zr - Bagdaulet Shugay; Lunara Rakhymbay; Aishuak Konarov; Seung-Taek Myung; Zhumabay Bakenov (Electrochemistry Communications, 2023)
The layered cathode material NaNi0.5Mn0.5O2 has attracted attention owing to its high capacity and high operating voltage. However, phase transitions make the electrodes susceptible to rapid capacity fading during cycling. In this study, Mn in NaNi0.5Mn0.5−xZrxO2 is partially substituted with Zr to stabilize the structure, resulting in an increased interlayer spacing for Na+ and an improved micro–nano-level structure with unhindered diffusion pathways. The Zr doping also suppresses the phase transformation (O3hex–O3′mon–P3hex–P3′mon–P3″hex), preventing volume change during cycling. The 3 %-Zr doped material showed a 25 % improvement in capacity retention after 70 cycles at 0.1C compared with the undoped material in the cut-off voltage range of 2.0–4.5 V. The doped material also exhibited improved reversibility of the phase transformations by increasing the inter-slab distance between layers, as confirmed by analysis of the lattice parameters.